Species profiles life histories and environmental requirements of coastal fishes and invertebrates (North Atlantic)--Atlantic tomcod - Stewart, Lance L. (U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.76)